Comparison of disability level between Early and Late Onset Parkinson’s Disease using WHODAS 2 - Nascimento, Isaíra Almeida Pereira da Silva; Nobrega, Kátia Cirilo Costa; Souza, Bruno Rafael Antunes; Barone, Isabela Carneiro; Checchio, Giovanna; Ponciano, Vitória Pereira; de Paula, Clara Greif Cerveira; Possani, Arieni Nunes; Penha, Natália Cardoso; Helene, André Frazão; Roque, Antonio Carlos; Savica, Rodolfo; et al. (Frontiers in Neurology, 2023)
Background Parkinson’s disease (PD) is a degenerative neurological disorder that usually affects people over the age of 60. However, 10%–20% of patients have an early onset of PD (EOPD). Objectives To compare disability levels according to the World Health Organization Disability Assessment Schedule 2.0 (WHODAS-2) between people with EOPD and those with late-onset PD (LOPD). Methods We conducted a cross-sectional study with 95 EOPD patients (mean-age 44.51 ± 4.63, H&Y 1.93 ± 0.93) and 255 LOPD patients (mean-age 63.01 ± 7.99, H&Y 2.02 ± 0.95). Demographic information, clinical characteristics, cognitive evaluation by Telephone-Montreal-Cognitive-Assessment (T-MoCA), functionality self-evaluation by WHODAS-2 and the Unified-Parkinson’s-Disease-Rating-Scale (MDS-UPDRS), parts I and II, were documented for each patient by an individual remote interview. Results Analysis showed a statistically significant difference between EOPD and LOPD in two domains of WHODAS-2 only: cognition (Z-adjusted = 2.60; p-value adjusted <0.009) and activities of daily living related to work/school (Z-adjusted = 2.34; p-value adjusted <0.01). T-MoCA scores confirmed more impaired cognition capacity in LOPD (Z-adjusted = 2.42; p-value adjusted <0.01). The two groups had no significant differences in levodopa daily dosage, Hoehn and Yahr (H&Y) stages, disease time duration, and MDS-UPDRS I and II scores. Conclusion People living with EOPD face similar disability levels as those with LOPD, except for cognition, where LOPD patients exhibited higher levels of disability than EOPD and for work activities where the EOPD exhibited higher levels of disability than LODP. These results highlight the challenges faced by people with EOPD in interacting with society and living with the disease for a longer time. The WHODAS-2 can be a useful tool to assess disability and tailor interventions for people with PD of different age groups.